Getting Life Expectancy Estimates Right for Pension Policy: Period versus Cohort Approach - Mercedes Ayuso; Jorge Miguel Bravo; Robert Holzmann (Institute of Labor Economics (IZA), 2018)
In many policy areas it is essential to use the best estimates of life expectancy, but such estimates are vital to most areas of pension policy – from indexed access age and the calculation of initial benefits to the financial sustainability of pension schemes and the operation of their balancing mechanism. This paper presents the conceptual differences between static period and dynamic cohort mortality tables, estimates the differences in life expectancy between both tables using data from Portugal and Spain, and compares official estimates of both life expectancy estimates for Australia, the United Kingdom, and the United States for 1981, 2010 and 2060. This comparison reveals major differences between period and cohort life expectancy in and between countries and across years. Using measures of period instead of cohort life expectancy creates an implicit subsidy for individuals of 30 percent or more, with potentially stark consequences on the financial sustainability of pension schemes. These and other implications for pension policy are explored and next steps suggested.
Keywords: D9; G22; H55; J13; J14; J16; 330; cross-country comparison; Lee-Carter; life expectancy indexation; balancing mechanism